Pitch y su aporte en el aprendizaje de los estudiantes del bachillerato técnico en informática de la Unidad Educativa del Milenio Carlos Alberto Aguirre Aviles, Periodo Académico octubre 2024 - marzo 2025 - Medina Arias, Merida Ivanna (2025)
This study analyzes the contribution of the use of Pitch in the learning of the students of technical baccalaureate in computer science of the educational unit of the Millennium Carlos Alberto Aguirre Avila during the academic period from October 2024 to March 2025. Pitch is a technological tool designed for the creation of interactive presentations, it was used as a support for the organization of academic projects and the improvement of skills such as: collaborative. The research was developed using a mixed approach by sending quantitative and qualitative techniques to elaborate both student perceptions and results in key areas such as creating effective presentations, group work and communication. The findings indicate that the platform enhances student motivation and participation by facilitating the clear organization of ideas and the development of communication skills. However, areas for improvement were identified as the need for additional training for the optimal use of some advanced functions of Pitch from the perspective of motivation most students reported a positive contribution to their academic engagement through interaction and work together, despite this a percentage of students showed a neutral stance emerging that additional strategies should be implemented to motivate their active participation. Pitch emerges as a valuable tool for pedagogical innovation contributing to the development of key skills in a digital and collaborative environment.